Stability prediction of early orthopedic treatment in Class III malocclusion: morphologic discriminant analysis - V. Paoloni; F. C. De Razza; L. Franchi; P. Cozza (SpringerOpen, 2021)
Abstract Background To evaluate morphologic differences between class III malocclusion success and failure treatment subjects in order to identify which variables are more predictive for long-term stability in early orthopedic treatment. In this retrospective study, 31 patients were enrolled from the Department of Orthodontics (Rome Tor Vergata). Inclusion criteria were as follows: white ancestry, class III malocclusion, mixed dentition, cervical stage (CS) 1-2, no pseudo-class III. Pre-treatment radiographic and cast records were collected. Each patient underwent rapid maxillary expansion/facial mask/bite block (RME/FM/BB) orthopedic treatment until correction. At T1 (permanent dentition, CS4), records were recollected. According to treatment stability, relapse group (RG, 19) and success group (SG, 12) were identified. Sagittal and vertical cephalometric and digital cast measurements were performed. Student's t tests were used for statistically significant differences inter and intra groups. For discriminant analysis, relapse or success status was added to each patient's T0 data. Results At T0, RG showed larger upper anterior transversal width (p = 0.0266), while at T1 the upper anterior length was shorter than SG (p = 0.0028). Between T1 and T0, both groups showed larger upper anterior and posterior transversal widths. SG had greater upper anterior (p = 0.0066) and posterior (p = 0.449) sagittal length. RG presented larger lower anterior (p = 0.0012) and posterior (p = 0.0002) transversal widths, while there were no differences in SG lower arch. Discriminant analysis provided two predictive variables with an accuracy of 80.6%: upper anterior length and upper posterior length. Conclusion A shorter and wider maxilla could be a predisposing factor for relapse and failure of the early orthopedic treatment of class III malocclusion patients. The absence of mandibular changes could be predictable for treatment success.